MIDWIFE CARE FOR TODDLERS WITH ACUTE DIARRHEA WITH PURE HONEY INTERVETION FOCUS AT PUSKESMAS TOROH 1 - Mariza Siti Zulichah; Rizki Sahara; Lalily Himawati (The Shine Cahaya Dunia Kebidanan, 2023)
Background; Definition Diarrhea is endemic in indonesia and is also a potential extraordinary event (KLB) whitch is often accompainied by death. Diarhhea is still a public health problem in indonesia. Under- five deaths due to diarhhea occur because they are not helped early and not given proper treatment. Theoretically, 10% of diarrhea sufferers will die to severe dehydration if no treatment is given. The purpose of this study was to determine whether the effect of pure honey on reducing the frequency of diarhhea in childdren under five. Method; The research design that the researcher uses is a case study research desugn. This descriptive case study research uses the subick participatory observation method. Result; The results showed that diagnosis of An.K with pure honey. Evaluation of the implementation of giving pure honey in An. K case by giving pure honey toreduce the frequency on consistency of diarhhea in toddlers. Conclusion; There is a decrease in the frequency and consistency of diarhhea in tollders after being given treatment with pure honey.